The fluency of human-robot collaboration based on human-robot fit - Zhu, Qi (International Journal of Global Economics and Management, 2024)
As an important working mode of current manufacturing enterprises, human-robot collaboration (HRC) is of great significance for enterprises to improve production efficiency and quality. However, unfortunately, there are still some problems in the practice of HRC, such as lack of fluency and low quality of HRC, which limit the positive role of HRC in manufacturing enterprises. Therefore, it is of great significance to study and reveal the influencing factors and formation mechanism of HRC fluency for further exerting the positive role of HRC and managing HRC in a targeted way. Building upon a review and analysis of existing literature, this study innovatively explores the formation process of human-robot collaboration fluence based on the theory of person-environment fit.